2008
DOI: 10.1111/j.1365-3091.2007.00926.x
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions and architecture of late Pleistocene submarine lobes off the northern margin of East Corsica

Abstract: Sandy lobe deposits on submarine fans are sensitive recorders of the types of sediment gravity flows supplied to a basin and are economically important as hydrocarbon reservoirs. This study investigates the causes of variability in 20 lobes in small late Pleistocene submarine fans off East Corsica. These lobes were imaged using ultra-high resolution boomer seismic profiles (<1 m vertical resolution) and sediment type was ground truthed using piston cores published in previous studies. Repeated crossings of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
279
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(291 citation statements)
references
References 43 publications
11
279
0
1
Order By: Relevance
“…Each environment is commonly associated with a particular geometry, facies, and bed thickness distribution (Mutti and Normark, 1987;Normark, 1978;Sullivan et al, 2000;Deptuck et al, 2008;Prélat et al, 2009;Hubbard et al, 2014;Stevenson et al, 2015). For example, submarine lobe deposits typically show a qualitative decrease in bed thickness, grain size, sand content, and amalgamation in proximal-to-distal and axis-to-margin transects (Normark, 1978;Sullivan et al, 2000;Deptuck et al, 2008;Prélat et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each environment is commonly associated with a particular geometry, facies, and bed thickness distribution (Mutti and Normark, 1987;Normark, 1978;Sullivan et al, 2000;Deptuck et al, 2008;Prélat et al, 2009;Hubbard et al, 2014;Stevenson et al, 2015). For example, submarine lobe deposits typically show a qualitative decrease in bed thickness, grain size, sand content, and amalgamation in proximal-to-distal and axis-to-margin transects (Normark, 1978;Sullivan et al, 2000;Deptuck et al, 2008;Prélat et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, submarine lobe deposits typically show a qualitative decrease in bed thickness, grain size, sand content, and amalgamation in proximal-to-distal and axis-to-margin transects (Normark, 1978;Sullivan et al, 2000;Deptuck et al, 2008;Prélat et al, 2009). However, the details of these downstream and lateral facies changes are often overlooked, and very few studies perform correlations at the bed scale (e.g., Chapin and Tiller, 2007;Marini et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Each coarse-grained package at Site M29 has its own thickness, ratio of glauconite to quartz sand, and grain-size distribution, which could suggest compensational stacking of lobe deposits (e.g., Prélat et al, 2009). Several studies have shown that compensational stacking of basin-floor elements can occur across a range of scales (e.g., Deptuck et al, 2008;Prélat et al, 2009;van der Merwe et al, 2014). It is striking that coreholes at both Sites M28 and M29, which are 9 km apart in a dip direction, intersected the same sharp-based coarse-grained deposits in all sequences, apart from m5.47 (Fig.…”
Section: Environments Of Deposition Of the Bottomsetsmentioning
confidence: 99%
“…The sediment input from the Tuscan Shelf is low since sediment from Italian rivers is mostly trapped in the shelf and cannot reach the Corsica Trough (Roveri 2002). Most of the sediment deposited in the Corsica Trough is transported from the Corsica shelf by the Golo turbidite network (Deptuck et al 2008; Fig. 1).…”
Section: Introductionmentioning
confidence: 99%